Extraction of Phenolic Total Compound and Determination of Antioxidant Activity of Cocoa Leaves Extracted Using Various Solvents - Subekti Hartiningsih; Supriyanto Supriyanto (The University of Lampung, 2023)
In the cultivation of cocoa plants there are by-products, one of which is cocoa leaves. This by-product comes from periodic pruning of cocoa plants which has not been utilized optimally. Phenolic compounds contained in the cocoa leaves are known as bioactive compounds which also have a role as antioxidants. The content of bioactive compounds in cocoa leaves can be extracted from plant tissues by extraction method. The objective of this research was to achieve cocoa leaf extract with the highest antioxidant content using the maceration method. Extraction by maceration on old cocoa leaves with a variety of solvents, namely methanol, acetone, and ethyl acetate. The results showed that the extract of old cocoa leaves with methanol as a solvent showed the highest content of polyphenolic compounds. A yield of 7,129% was attained from old cocoa leaves with total phenolic content of 349,952 ± 0,051 mg EAG/g sample, EC 50 antioxidant value of 287,958 ± 0.144, and antioxidant activity of 86,928 % RSA. The yield of phenolic compounds and antioxidant activity contained in cocoa leaf extract (sequentially from the highest) were obtained with methanol solvent, followed by acetone and ethyl acetate solvents. Keywords: Antioxidant activity, Bioactive, Cocoa leaf, Methanol solvent, Yield